2017
DOI: 10.1111/jce.13168
|View full text |Cite
|
Sign up to set email alerts
|

Early Canadian Multicenter Experience With WATCHMAN for Percutaneous Left Atrial Appendage Closure

Abstract: In our early Canadian experience, WATCHMAN for LAA closure in patients contraindicated to anticoagulation appeared safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 17 publications
2
29
2
Order By: Relevance
“…Many authors indicated that patient eligibility was dependent upon the clinical indication ( Amat-Santos et al 2015 ; Basmadjian et al 2016 ; Campelo-Parada et al 2016 ; Chu et al 2016 ; de Varennes et al 2016 ; Gonzalez-Barlatay et al 2017 ; Peters 2002 ; Rodés-Cabau et al 2010; Sapp et al 2013 ; Saw et al 2015 , 2017 ; Webb et al 2006 ). Peters (2002) explained that MDSAP “provides approval for the use of silicone gel implants for the following patients: mastectomy, augmentation after failed saline implants (usually with ripples and folds) and primary augmentation if a saline failure is strongly predicted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors indicated that patient eligibility was dependent upon the clinical indication ( Amat-Santos et al 2015 ; Basmadjian et al 2016 ; Campelo-Parada et al 2016 ; Chu et al 2016 ; de Varennes et al 2016 ; Gonzalez-Barlatay et al 2017 ; Peters 2002 ; Rodés-Cabau et al 2010; Sapp et al 2013 ; Saw et al 2015 , 2017 ; Webb et al 2006 ). Peters (2002) explained that MDSAP “provides approval for the use of silicone gel implants for the following patients: mastectomy, augmentation after failed saline implants (usually with ripples and folds) and primary augmentation if a saline failure is strongly predicted.…”
Section: Resultsmentioning
confidence: 99%
“…The MDSAP approves the use of unlicensed alternatives to licensed medical devices when they are perceived to be clinically superior ( Almashham et al 2008 ; Abraham et al 2012 ; Bagur et al 2016 ; Campelo-Parada et al 2016 ; Humpl et al 2010 ; Nietlispach et al 2010 ; Raymond et al 2001 ; Regueiro et al 2017 ; Ricci et al 2017 ; Saw et al 2017 ). Peters' (2002) review of breast implants noted the availability of two types of implants: saline-filled (comprising 95% of implants), which were licensed, and gel-filled (5%), which, at the time, were unlicensed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the implant success rate improves significantly as operator experience increases and techniques improve. This rate increased from 88% in the Watchman Left Atrial Appendage System for Embolic Protection in Patients with Atrial Fibrillation PROTECT AF) trial (11) to 95% in the Prospective Randomized Evaluation of the Watchman Left Atrial Appendage Closure Device in Patients with Atrial Fibrillation in Patients With Atrial Fibrillation Versus Long-Tern Warfarin Therapy (PREVAIL) trial (10), 97.2% in the Canadian experience (14), and then improved to 98.5% in the Registry to Evaluate Real-Word Clinical Outcomes in Patients With Atrial Fibrillation and High Stroke Risk-Treated With the Watchman Left Atrial Appendage Closure Technology (EWOLUTION) (15). Overall, successful implant placement is achieved in 88%–98.5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian multicenter experience with Watchman for percutaneous LAAC conducted by Saw et al reported pooled consecutive series of patients who underwent Watchman LAAC at four major Canadian centers. In this study, 20) they included 106 patients who had the Watchman implant starting from May 2013 up to October 2015. The primary objective of the study was to evaluate the safety and efficacy of the Watchman device.…”
Section: Trials and Studies Looking At Efficacy And Safety Of Watchmamentioning
confidence: 99%